From Phenomenology to Liberation: The Displacement of History and Theology in Levinas’s Totality and Infinity - Meskin, Jacob (Philosophy & theology, 1989)
The paper seeks to establish a kinship between the philosophy of Levinas and the theology of liberation. In their separate domains, these two enterprises reveal to us a portrait of late, twentieth-century intellectual work which refuses to abandon eschatological urgency. Philosophy and theology may meet, outside of both of their own homes, on a journey toward the other, in ethics.